Exploration of a Postbiotic Derived from Enterococcus faecium HDRsEf1 and Its Probiotic Mechanisms - Yingying Chen; Yingting You; Lizhen Ren; Guilin Fu; Naiji Zhou; Yuncai Xiao; Deshi Shi (Microorganisms)
This study aimed to identify the heat-resistant bioactive components of Enterococcus faecium HDRsEf1 (HDRsEf1) and investigate their beneficial mechanism. Heat-treated culture supernatants of HDRsEf1 significantly suppressed CXCL-1 expression in LPS-stimulated MODE-K cells (p < 0.001), indicating the presence of heat-resistant anti-inflammatory components. Crude protein (P-Ef1) and crude expolysaccharide (EPS-Ef1) were isolated from an HDRsEf1 culture supernatant using ammonium sulfate and ethanal precipitation. Critically, only crude EPS-Ef1 retained an anti-inflammatory effect after heat treatment, while crude P-Ef1 lost this activity. Further investigation revealed that crude EPS-Ef1 (25 μg/mL) promoted MODE-K cell proliferation via EdU assays (p < 0.001), potentially through an upregulation of PCNA mRNA expression (p < 0.001). Animal studies demonstrated that an oral administration of crude EPS-Ef1 (4 mg/kg bw, 14 days) significantly increased body weight gain and jejunal crypt depth (p < 0.05) while reducing intestinal CXCL-1 mRNA levels (p < 0.001). These in vivo findings are consistent with in vitro observations. A structural analysis using HPAEC and SEC-MALLS-RI characterized crude EPS-Ef1 as a heteropolysaccharide (Mw 80.3 kDa) with a near-spherical conformation (slope 0.13) composed of mannose, glucose, glucuronic acid, and galactose (5.4:4.4:1.2:1). In summary, this study identifies crude EPS-Ef1 as the heat-resistant postbiotic component. Crude EPS-Ef1 possesses the dual effects of suppressing intestinal inflammation and promoting intestinal epithelial cell proliferation, which provides a theoretical foundation for a crude EPS-Ef1-based postbiotic.